Causal association between body mass index and temporomandibular disorders: a bidirectional two-sample Mendelian randomization analysis - Xin Chen; Zheng Cheng; Junyu Xu; Zhibai Zhao; Qianglin Jiang (BMC, 2023)
Abstract Background Observational studies have shown that body mass index (BMI) is highly correlated with the occurrence of temporomandibular disorders (TMDs). However, these studies failed to present a causal relationship. Thus, we aimed to performed a Mendelian randomization (MR) study to investigate causality between BMI and TMDs. Methods We performed a two-sample bidirectional MR analysis using large-scale genome-wide association studies (GWAS). Data were obtained from a large-scale BMI dataset (N = 322,154), TMDs dataset (N = 134,280). The causal effects were estimated with inverse-variance weighted (IVW) method, MR Egger, weighted median. Sensitivity analyses were implemented with Cochran's Q test, MR-Egger intercept test, MR-PRESSO, leave-one-out analysis and the funnel plot. Results In the forward MR analysis, a genetic prediction of low BMI was causally associated with a higher risk of TMDs (IVW OR: 0.575, 95% CI: 0.415-0.798, p: 0.001). Similar results were obtained using other complementary methods (MR Egger OR: 0.270, 95% CI: 0.104-0.698, p: 0.009; weighted median OR: 0.496, 95% CI: 0.298-0.826, p: 0.007). In the reverse MR results, TMDs was shown to have no significant effect on BMI (all p > 0.05). No pleiotropy and heterogeneity were detected in the bidirectional analysis (p > 0.05). Conclusion A lower BMI might be causally associated with increased risk of TMDs, supporting the importance of weight control for the prevention of TMDs. Clinicians should pay more attention to the low-BMI patients among those seeking medical advice due to temporomandibular joint discomfort.